(3cJGH GdWgGQI aj GdMceI GdYedjIs - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s
(3ChdgG (B:s
(3GdebGdI GdChdi bGd CMeO Hf eMeO eSchjg ZQVfG ai gPG GdcJGH s
(3BNQgG (B:s
(3hgh jROGO HgPg GdCTjGA bhI hjSJajO s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1436s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs